Gene co-expression network analysis of the transcriptome identifies cold-resistant hub genes related to carbohydrate metabolism in peach fruit - Deng, Xianzhu; Wei, Yingying; Chen, Yi; Ding, Phebe; Xu, Feng; Shao, Xingfeng (Elsevier B.V., 2025)
In order to explore the key factors involved in the regulation of chilling injury formation in carbohydrate metabolism of peach fruit, we systematically analyzed the response of peach fruit to cold stress from physiological and transcriptomic perspectives. Cold stress in peach elevated malondialdehyde, impaired membranes, reduced sucrose via invertase-mediated hydrolysis to fructose/glucose, and may activate pentose phosphate pathway while inhibiting glycolysis pathways for metabolic maintenance and energy conservation, as suggested by phosphofructokinase and glucose-6-phosphate dehydrogenase activity shifts. Transcriptome and weighted gene co-expression network analysis revealed a series of genes respond to low-temperature stress in starch and sucrose metabolism pathway, including vacuolar invertases gene (PpVIN), hexokinase gene (PpHXK), trehalose-phosphate synthase gene (PpTPS), trehalose-phosphate phosphatase gene (PpTPP), and fructokinase gene (PpFRK), of these hub genes have been reported to resist to cold stress. In addition, by constructing co-expression network, several transcription factors (TFs) were involved in regulating hub genes related to carbohydrate metabolism in peach fruit, such as ZAT12, bZIP23, bZIP53, CBF5, and others. These TFs may serve as key regulators of the transcriptional network, modulating gene expression related to carbohydrate metabolism in response to cold stress.